Analysis of impact of manufacture technology on the exploitation properties of powder antifriction materials for printing machines - Віцюк, Юлія Юріївна (Technology audit and production reserves, 2015)
The article presents the research results of the effect of technological modes of manufacturing on the functional properties of new antifriction powder materials based on copper with a solid lubricant CaF2. It was shown that the developed technology for manufacturing of new antifriction materials based on powder metallurgy techniques ensured the formation of a fine-grained heterogeneous structure, which gives the material a high level of tribological properties. New powder material is much higher than the known cast bronze for antifriction characteristics. Friction films – secondary structures have been researched, they provide a self-lubricating effect. Micro-X-ray analysis showed the presence in friction films the chemical elements of the new material, counterface and air. It was studied the ratio of chemical elements in the friction films, which ensures the implementation of the self-lubricating effect. New powder materials based on copper and alloyed by nickel, with additives of solid lubricant – CaF2 can be successfully used in high-speed friction units of printing machines. Developed technological modes cause the formation of structure which is capable to ensure a high level of operational properties of sliding bearings, which are used in friction units of printing equipment.